IP telephony unveiled - Brown, Kevin (Network business series., 2004)
Understand how IP telephony can change your business This book explains four key points to help you successfully implement your IP telephony strategy: IP telephony works today. This is not new, unproven technology. Thousands of customers have implemented IP telephony successfully. So can you. Expect to save money. IP telephony may well cost your organization money-initially. But the business impact and post-installation process improvements give you a significant and rapid return on your investment. It's more than voice over IP. You'll understand the difference between voice over IP (VoIP) and IP telephony and what that means for your business. This is critical. They are not the same. It's more than a dial tone. There are potential business-impacting applications within your own organization. IP Telephony Unveiled helps you recognize these applications. The emerging IP telephony market is fraught with misunderstandings and misinformation. IP telephony can impact a company's business model in tremendous ways. It can open new revenue streams, enhance profitability, drive new levels of customer and employee satisfaction, and be a key enabler in a company's strategy to differentiate itself competitively-but only if you're aware of these benefits. IP Telephony Unveiled is written for all those responsible for corporate strategies for revenue generation, cost containment, and customer satisfaction. IP Telephony Unveiled uncovers the value behind this technology, which helps you see past what might appear to be only a new telephone system, to understand the strategic enabler laying dormant in many companies' networks. Through this book, you will understand the real benefits of an IP telephony strategy and get assistance in developing this strategy inside your organization. This volume is in the Network Business Series offered by Cisco Press. Books in this series provide IT executives, decision makers, and networking professionals with pertinent information on today's most important technologies and business strategies.